Melatonín a srdce - Vazan, R; Béder, I; Styk, J (Ceskoslovenska fysiologie, 2004)
Evidence gathered during the last years shows that the pineal hormone melatonin participates in the regulation of the heart. Melatoninergic receptors were found in the heart and vessels and also in the higher centers involved in the regulation of cardiovascular system. Melatonin protects the heart against ischaemia-reperfusion injury and also against cardiotoxic effects of adriamycin and alloxan. Lack of melatonin was repeatedly reported in patients with coronary heart disease. Intake of this hormone leads to decrease of blood pressure in normotensive and hypertensive subjects, while pinealectomy induces hypertension. In addition melatonin can probably influence the levels of intracellular calcium in cardiomyocytes. The aim of this review is to summarize available evidence about effects of melatonin on the heart. Mechanisms involved in these effects are also suggested.
Keywords: melatonin; Humans; zvířata; Heart; Animals; Melatonin; lidé; srdce